國小自然科教師學習兩種探究式教學法與抉擇應用 The Primary Science Teachers Learn Two Kinds of Inquiry Teaching Methods and Choice Application - 盧秀琴 Chow-Chin Lu; 劉靜文 Ching-Wen Liu (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2021)
因應 12 年國教強調探究與實作的改革，本研究以「昆蟲生理學特論」課程培育 14 位國 小自然科教師兩種探究式教學法，探討其學習成效與抉擇應用的考量。本研究培育內容 包含：講授昆蟲學理論、探究式教學法理論、示範教學，以及國小自然科教師抉擇一種 教學法設計實驗教案與微型教學，並設計戶外教學學習單；本研究使用 PO+E 微型教學 評量或 POEST 微型教學評量予以評量，並訪談他們抉擇應用探究式教學法的想法。結果 顯示：一、四組使用 PO+E 教學法微型教學，三組使用 POEST 教學法微型教學，評量達到優良等級，表示能掌握探究式教學法的精髓。二、自然科教師學習探究式教學法後，所設計的教案能先鋪陳教學情境，使用簡報建構基本知識後再讓學生預測；其次、設計的實驗包含探究與實作，讓學生根據實驗紀錄去修正預測的錯誤理由。三、自然科教師 抉擇 PO+E 教學法是因為「科學解釋能力」六格容易撰寫，探討「科學原理」使得科學實驗更有意義。四、自然科教師抉擇 POEST 教學法是因為能引導學生使用 2 個實驗證據證明自己的主張，避免淪為主觀。 In response to Taiwan’s 12-year Basic Education plan, which emphasizes the reform of inquiry and implementation, this study used an "Advanced Entomology Physiology" course to train 14 primary science teachers to study two methods of inquiry teaching, where the teachers observed the learning effectiveness of the two methods, and selected the application they felt met their teaching needs. The nurturing contents included: teaching the theory of entomology and two inquiry-based teaching methods, as well as demonstration teaching, then the primary science teachers selected their preferred teaching method to design teaching and micro-teaching plans. This study used the Micro Teaching Assessment of PO+E (MTAP) and the Teaching Assessment of PO+E, as well as scientific explanations with text scaffolding (MTAPS), to evaluate the micro-teaching plans, and interviewed the participants regarding their thoughts. The results, are as follows. First, four groups selected the PO+E teaching method for micro-teaching, while three groups selected the POEST teaching method for micro-teaching. The assessment results achieved the excellent level, indicating that they could master the inquiry teaching methods. Second, after learning the two inquiry teaching methods, the primary science teachers first arranged their teaching situations and constructed lessons regarding the basic required knowledge, and then encouraged the students to predict the outcomes. The teachers found that they could design inquiry guidelines, as implement experiments, and remind students to correct the wrong reasons for their predictions, as based on the experimental records. Third, some primary science teachers selected the PO+E teaching method because the "science interpretation ability" made it easy to write lesson plans, and the exploration of "scientific theory" in class made the scientific experiments more meaningful. Fourth, primary science teachers selected the POEST teaching method because they could guide lines for students to apply 2 experimental evidence methods to prove their claims and avoid becoming subjective.